SOCIAL-PEDAGOGICAL AND METHODOLOGICAL ASPECTS OF THE DEVELOPMENT OF ACADEMIC FREEDOM OF FUTURE TEACHERS - Shaxlo Xudaykulova Mamaniyozovna, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article details the nature of academic freedom and the educational strategies used to develop it. It is emphasized that academic freedom is primarily about creating opportunities for free thinking, critical thinking and independent research in education.The article shows the importance of such educational approaches as the formation of personal responsibility, independent decision-making, critical analysis, creative thinking and teamwork in ensuring academic freedom.